Synthesis And Characterization Of Cuo Doped Zno Composite Photovoltaic Thin Film: Effect Of Cuo Content - Nazira Binti Mohd Zahir (2022)
DSSCs (dye-sensitized solar cells) have emerged as financially and technically viable solution to p-n junction photovoltaic systems. Copper oxide and zinc oxide P-type semiconductors are main operating materials utilized in solar cells. CuO is an appealing choice solar absorber because of its strong solar absorbance and small thermal emittance. This paper explains the solid-state reaction synthesis and characterization of semiconducting particles, specifically ZnO. The 'UV visible absorption spectra were used to investigate optical characteristics and band gap. According to XRD analysis, the CuO doping caused the lattice constants to shift to a certain amount. These findings reveal that the energy band gap reduces with increasing annealing temperature, which can be attributed to the samples' improved crystallinity and also increasing mol percentage of CuO also reducing band gap. Dopants can be used to tailor the band gap of CuO—ZnO 4.25-4.71 eV, 4.00-3.77 eV and 3.28-2.56 eV, respectively. Keywords: Dye-sensitized solar cells, Photovoltaic, Solid-state reaction, CuO, ZnO, Band gap.